PROCESS FOR MAKING TURBINE PROPELLER SHAFT USING ST.37 LOW CARBON STEEL MATERIALS AT THE INDONESIAN INSTITUTE OF KNOWLEDGE (LIPI) - Fajri Hamdani, Mohamad; Dewi Jannati, Eidelweis (Universitas Majalengka, 2022)
The shaft is a rotating stationary member, usually spherical in cross section, the shaft may receive bending loads, tensile loads, compressive loads or torsional loads acting alone or in combination with one another. The propeller turbine shaft is made using a conventional lathe from the Indonesian Institute of Sciences (LIPI). The shafts made have stratified diameters with diameters of 8 mm, 10 mm, 15 mm and 24 mm with an overall length of 595 mm and has a thread in one part of the shaft. The axle uses ST.37 material, dural rod material and for the outside of the shaft (casing) using aluminum. Dural is a high strength aluminum based alloy with the addition of copper, magnesium and manganese.